Fears and fascinations : representing Catholicism in the American South - Haddox, Thomas F. (Thomas Fredrick) (Fordham University Press, 2005)
Looking at the works of diverse writers as the gens de couleur libre poets of antebellum New Orleans, this book focuses on the shifting and contradictory ways Catholicism has signified within Southern literature and culture. It contributes to a more nuanced understanding of American and Southern literary and cultural history.